Biologically inspired modelling for the control of the upper limb movements: from concept studies to future applications - Conforto, Silvia; Bernabucci, Ivan; Severini, Giacomo; Schmid, Maurizio; D'Alessio, Tommaso (Frontiers in Neurorobotics, 2009)
Modelling has recently been exploited for gaining knowledge on the mechanisms of motor control. Computational models, simulating the behaviour of complex systems, have often been used in combination with soft computing strategies, thus shifting the rationale of the modelling from the description of a behaviour to the understanding of the mechanisms behind it. In this context, computational models are preferred to deterministic schemes because they deal better with complex systems. The literature offers some biological inspired models, which perform better than traditional approaches when dealing with both learning and adaptivity mechanisms. Can these theoretical studies be transferred into an application framework? That is, can biologically inspired models be used to implement rehabilitative devices? Some evidences, even if preliminary, are presented here, and allow an affirmative answer to the previous question, thus opening new perspectives.